Human serum albumin capsulated hydrophobic carbon nanodots as staining agent on HeLa tumor cell - Fahmi, Mochamad Zakki; Wibowo, Denika Liyan Nor; Sakti, Satya Candra Wibawa; Lee, Hwei Voon; Isnaeni, - (Elsevier, 2020)
The hydrophobic carbon nanodots (CDs) are promising nanoparticles to develop due to its uniformly size, good photoluminescence properties, and easy surface-modification. Highly photoluminescent hydrophobic CDs have been synthesized by carbonization of tartaric acid–L-tyrosine precursors. These hydrophobic CDs showed uniformly size distribution and exhibited strong–blue emission under UV irradiation. Further surface modification using human serum albumin (HSA) lead to the formation of hydrophilic CDs-HSA within low toxicity and good colloidal stability over varied pH and high ionic strengths. Various spectroscopies characterizations were done to analyze the morphological and chemical composition of both CDs and CDs-HSA. Further improvement analyses on cytotoxicity and confocal laser microscopy (CLSM) upon HeLa tumor cell suggested that the designed CDs-HSA was effective to be applied as staining agent against tumor cells. © 2019 Elsevier B.V.